Strategies to get students to recognize and use past tense in their affirmative and interrogative forms. - Delgado Loaiza, Cristina Lisbeth (My University, 2019)
This project focuses on the application of different methodological strategies that help the teacher to develop how to learn in a better way the past tense in its affirmative and interrogative forms applying to all students. This way it will be a little easier for the student to learn it and the teacher to explain it. The objective is to provide teachers with methodological strategies through active, innovative and motivating techniques to achieve quality teaching - learning. This research supports all teachers to guide students on the correct use of past tense in their affirmative and interrogative forms, in such a way that I have developed three very important skills; Reading, speaking, listening.
Este proyecto se centra en la aplicación de diferentes estrategias metodológicas que ayudan al docente a desarrollar como aprender de una mejor manera el tiempo pasado en sus formas afirmativas e interrogativas aplicando a todos los estudiantes. De esta manera se les hará un poco más fácil, tanto como para el estudiante aprenderlo y el profesor explicarlo. El objetivo del mismo es proporcionar a los maestros estrategias metodológicas a través de técnicas activas, innovadoras y motivadoras para lograr una enseñanza - aprendizaje de calidad. Esta investigación sirve de apoyo a todos los docentes para guiar a los estudiantes sobre el uso correcto del tiempo pasado en sus formas afirmativas e interrogativas, de tal manera que he desarrollado tres habilidades muy importantes; Reading, speaking, Listening.
Keywords: STRATEGY; TECHNIQUE; MOTIVATION; LEARNING